Tailoring MXene/nickel cobalt phosphate composite for enhanced electrochromic and supercapacitor applications - Mustafa, Muhammad Norhaffis; Mohd Abdah, Muhammad Amirul Aizat; Saidi, Norshahirah Mohamad; Numan, Arshid; Sulaiman, Yusran; Walvekar, Rashmi; Khalid, Mohammad (John Wiley and Sons, 2025)
Electrochromic materials that simultaneously enable optical modulation and charge storage offer a promising route toward multifunctional energy systems. Herein, we report a scalable synthesis of a nickel cobalt phosphate–MXene (NCP/Ti3C2) composite engineered to couple fast ion transport with structural robustness. Using microwave-assisted deposition followed by spin coating, we constructed a conductive Ti3C2 network that intimately overlays the NCP matrix, forming an architecture that overcomes the transport limitations and instability typically observed in MXene–phosphate hybrids. The optimized NCP/Ti3C2 film delivered a high coloration efficiency (~140 cm2/C) and retained over 75% of its optical contrast after 1000 switching cycles. It further exhibits an exceptional specific capacitance (~2300 F/g at 1 mV/s), reflecting markedly enhanced charge-storage kinetics. Assembled into an asymmetric electrochromic supercapacitor with activated carbon, the device achieved an energy density of ~15 Wh/kg at a power density of ~1600 W/kg and maintained ~85% capacitance retention over 5000 cycles. These combined optical and electrochemical performances position the NCP/Ti3C2//AC system as a compelling platform for next-generation wearable and multifunctional energy-storage technologies.